2020
DOI: 10.1016/j.jpain.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin on Placebo and Nocebo Effects in a Pain Conditioning Paradigm: A Randomized Controlled Trial

Abstract: Highlights Placebo analgesia and nocebo hyperalgesia can be induced by classical conditioning. Oxytocin does not enhance placebo effect or decrease nocebo effect. Oxytocin does not influence extinction of placebo and nocebo responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Some studies have reported that intranasal oxytocin can enhance placebo analgesia [4] and even generate both placebo and nocebo effects in working memory performance [5] in men. However, several other recent studies on men [6] and women [7,8] found no evidence for effects of oxytocin. In an attempt to resolve these conflicting results Liu et al [9] have systematically re-evaluated the effects of intranasal oxytocin on placebo analgesia across sexes, dosages, and placebo effect induction paradigms in a large sample of subjects.…”
mentioning
confidence: 78%
“…Some studies have reported that intranasal oxytocin can enhance placebo analgesia [4] and even generate both placebo and nocebo effects in working memory performance [5] in men. However, several other recent studies on men [6] and women [7,8] found no evidence for effects of oxytocin. In an attempt to resolve these conflicting results Liu et al [9] have systematically re-evaluated the effects of intranasal oxytocin on placebo analgesia across sexes, dosages, and placebo effect induction paradigms in a large sample of subjects.…”
mentioning
confidence: 78%
“…In a more recent study, it was found that 24 IU of oxytocin did not enhance placebo analgesia in females [7]. Most recently, Skvortsova et al [8] found that 40 IU of oxytocin did not influence placebo analgesia and nocebo hyperalgesia responses in males. The links between oxytocin and placebo/nocebo remain to be established.…”
Section: Karger@kargercommentioning
confidence: 94%
“…The evidence from such studies is presently equivocal. For men, two studies indicate that intranasal oxytocin administration enhances placebo effects induced by verbal description (for analgesia [ 127 ] and working memory [ 128 ]), while three studies indicate that it does not (for analgesia induced by verbal description combined with conditioning [ 129 131 ]). For women, the results are less ambiguous, with three studies indicating that intranasal oxytocin administration does not enhance placebo analgesia, induced by verbal description [ 132 ], or verbal description combined with conditioning ([ 130 , 131 ]; [ 131 ] controlled for menstrual phase).…”
Section: Oxytocin Biology and The Identification Of Placebo Effectsmentioning
confidence: 99%